A New Deal for Global Health R&D? The Recommendations of the Consultative Expert Working Group on Research and Development (CEWG) - Røttingen, John-Arne (Public Library of Science, 2012)
John-Arne Røttingen and Claudia Chamas, chairs of the the Consultative Expert Working Group on Research and Development (CEWG), summarize their recent report recommending to the World Health Assembly that a global health R&D treaty be developed.